2015
DOI: 10.1007/s13202-015-0206-6
|View full text |Cite
|
Sign up to set email alerts
|

Research on a temporary plugging agent based on polymer gel for reservoir acidification

Abstract: A temporary plugging agent based on polymer gel was successfully prepared for temporary plugging in acidizing treatment. The gelation time, gel-breaking time, viscosity changes, temporary plugging capacity, and permeability recovery capacity were investigated. Increasing the polymer and cross-linker concentration reduced the gelation time of the polymer gel and temporary plugging agent, but caused difficulties in breaking the temporary plugging agent. Ammonium persulfate (APS) could be the driving force for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…After years of development, there are many types of temporary plugging agents, mainly divided into the following four types. They are granular TPA (Liu et al 2020;Shi et al 2020), fiber-type TPA (Zhang et al 2019b, c), gel-type TPA (Nasiri et al 2018;Zhao et al 2016), and compound TPA (Li et al 2020;Liu et al 2020).…”
Section: Edited By Yan-hua Sunmentioning
confidence: 99%
“…After years of development, there are many types of temporary plugging agents, mainly divided into the following four types. They are granular TPA (Liu et al 2020;Shi et al 2020), fiber-type TPA (Zhang et al 2019b, c), gel-type TPA (Nasiri et al 2018;Zhao et al 2016), and compound TPA (Li et al 2020;Liu et al 2020).…”
Section: Edited By Yan-hua Sunmentioning
confidence: 99%
“…The thickened acid system has a certain viscosity and small friction, which can effectively control the acid–rock reaction rate. However, the insufficient temperature resistance of thickened acid limits its application in the acid fracturing of high-temperature wells [ 14 , 15 , 16 , 17 ]. After investigation, it was found that the temperature resistance of the existing thickened acid was basically below 140 °C [ 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…For the use of conventional polymer gel temporary plugging agents, the dosage of the crosslinking agent is crucial. A low crosslinking agent dosage leads to considerably low plugging strength, while a high dosage damages the formation. , …”
Section: Introductionmentioning
confidence: 99%
“…A low crosslinking agent dosage leads to considerably low plugging strength, while a high dosage damages the formation. 13,14 Different from the traditional temporary plugging agent, the supramolecular gel temporary plugging agent is based on the theory of supramolecular chemistry. It utilizes the temperature responsiveness of the thermally induced supramolecular gel to avoid the drawbacks of the conventional gel temporary plugging agent.…”
Section: Introductionmentioning
confidence: 99%